ANALYSIS OF RESULTS OF STATE PROGRAMS ON DEVELOPMENT AND DEVELOPMENT OF THE FAR EAST - Y. Ionova (Вестник университета)
The development of the Far East is not only a significant historical phenomenon, but it is also a unique example of the economic development of one of the richest regions in terms of natural resources. The article analyzes the main provisions of state programs, which have been implemented throughout the entire historical period of development of the Russian Far East. The article describes the main program activities, amount of financing and strategic objectives that should be achieved as a result of implementation of the above mentioned programs. The article evaluatesthepresent-day initiatives and tendencies as well as the prospects of the current state programs and measures concerning the economic development of the region.